Measurements of global and local effects of wave impact on a fixed platform deck. (February 2017) - Abdussamie, Nagi; Ojeda, Roberto; Thomas, Giles; Amin, Walid
This article describes a series of model tests conducted to examine extreme wave events associated with tropical cyclonic conditions and their impacts on an offshore deck structure. Extreme waves of a representative cyclonic sea state were examined in a towing tank within long-crested irregular wave trains. Experimental results presented include global forces and localised slamming pressures acting on a rigidly mounted box-shaped deck, which represents a simplified topside structure of a tension leg platform. The effect of static set-down on the still-water air gap was investigated by applying an equivalent reduction for the deck clearance. It was found that a small reduction of 20 mm (2.5 m full scale) in the original deck clearance can lead to a doubling of the magnitude of the horizontal force and the vertical upward-directed force components, as well as significantly increased slamming pressures in many locations on the deck underside.